Circumflex Nuclear Configurations in Yucatecan Spanish as a Supraregional Feature: The Roles of Bilingualism and Gender. (December 2022) - Uth, Melanie; Martínez García, Nuria
In this paper, we study the nuclear configurations of declarative broad focus utterances in Yucatecan Spanish, a Mexican variety spoken in southeast Mexico in contact with Yucatec Maya, from a sociolinguistic perspective. We draw on a corpus of 276 utterances elicited from 16 speakers, eight Maya–Spanish bilinguals (four female/four male) and eight Spanish monolinguals (four female/four male). We particularly concentrate on the roles of bilingualism, gender, and their relationship to local (Hispanic) identity. Although the intonation of Yucatecan Spanish is known to be very different from Central Mexican Spanish, we find in our data a considerable number of contours that Martín Butragueño (2017) refers to as typical "Central Mexican circumflex intonation" (p. 153). What is more, this feature is distributed unevenly among speaker groups in our data. First of all, it is much more frequent in the bilingual than in the monolingual group. We suggest that this is due to the monolinguals' higher degree of identification with the local Spanish language and culture (whereas the bilingual speakers are more oriented toward the Mayan language and culture and less toward the local Spanish ones; see Uth, 2018b). Secondly, as regards gender, there are many sociolinguistic works that suggest that women tend to be less oriented toward local vernaculars than men. Building on that, we argue that a greater decrease of the supraregional circumflex configuration within the monolingual male group than within the monolingual female is to be expected. However, this hypothesis is not confirmed by our data.